An analysis words in english short stories through british council kids application - Permata, Divia Atma (Maliki Interdisciplinary Journal, 2026)
The study shows how important language structure is to developing narrative and character, and how important it is for translators to strike a balance between accuracy and cultural acceptability. In addition, the study looks at the use of compound words in English short stories available on the British Council Kids software. Particular emphasis is placed on the role of compound words in improving children’s English vocabulary and comprehension. There are three types of compound words: closed compound words (such as “notebook”), open compound words (such as “ice cream”), and hyphenated compounds. The study investigates three stories: “Elizabeth I,” “The Ugly Duckling,” and “Nessie - The Loch Ness Monster.” and finds key compound words and their meanings. The results show that these words enhance the narrative, support character development, and convey themes. Ultimately, this helps children’s language skills and comprehension. This article emphasizes the importance of short stories as a teaching tool to engage young students and enhance their understanding of compound words in context.